2021
DOI: 10.5937/jaes0-28528
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the effect of wheeled tractors and skidded timber bunches on forest soil compaction

Abstract: An increasing demand for forest products incites a large number of log transportation operations, which may lead to negative consequences for the soil and the ecosystem as a whole. This paper is focused on establishing a mathematical model to estimate the soil deformation and compaction processes under tires of wheeled forest machines and individual components of the skidding system such as forwarder, limbs, butts, and tops of tree-lengths in high latitudes, permafrost soil and forests. The method applied is b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…This aligns with our observation of a higher water table in disturbed plots across different age classes. We also found that harvesting has altered soil bulk density, increased water retention by reducing mesopore volume, which is common in mineral soils after machinery impact (Cambi et al 2015;Frey et al 2009;Grigorev et al 2021;Magagnotti et al 2012), leading to increased anaerobic conditions. However, we did not find any significant difference in the net emissions of CH4 between the ruts and the adjacent non-impacted control areas.…”
Section: Impact Of Harvesting Machines On Peat and Vegetationmentioning
confidence: 66%
“…This aligns with our observation of a higher water table in disturbed plots across different age classes. We also found that harvesting has altered soil bulk density, increased water retention by reducing mesopore volume, which is common in mineral soils after machinery impact (Cambi et al 2015;Frey et al 2009;Grigorev et al 2021;Magagnotti et al 2012), leading to increased anaerobic conditions. However, we did not find any significant difference in the net emissions of CH4 between the ruts and the adjacent non-impacted control areas.…”
Section: Impact Of Harvesting Machines On Peat and Vegetationmentioning
confidence: 66%
“…Earlier, harvesting has been found to alter soil bulk density and increase water retention due to the reduction of mesopore volume (Lepilin et al 2019), which hinders soil aeration. This is common on mineral soils after machinery impact (Frey et al 2009;Magagnotti et al 2012;Cambi et al 2015;Grigorev et al 2021) and leads to increased anaerobic conditions. Yet again, we observed no difference in the net emissions of CH 4 between the ruts and the adjacent non-impacted control areas.…”
Section: Discussionmentioning
confidence: 99%
“…There is therefore an urgent need to identify the machine-based forest operations with the smallest impact on soils in order to ensure sustainable forest management (Marchi et al 2018;Schweier et al 2019;Picchio et al 2020). The aim of many studies has been to assess and reduce the impact of harvesting and extraction machines on forest soils (Sakai et al 2008;Labelle and Jaeger 2011;Abdi et al 2017;Giannetti et al 2017;Cambi et al 2018;Labelle et al 2018;Grigorev et al 2021), and effective technological solutions have been developed (Engler et al 2021), such as the use of machines equipped with bogie tracks (Edlund et al 2013;Cambi et al 2016;Ala-Ilomäki et al 2021).…”
Section: Introductionmentioning
confidence: 99%